The Affective Aspects of The Use of Media On The Leaner - Suwarsih Madya (LPMPP Universitas Negeri Yogyakarta, 1982)
Education should keep up with societal changes. If students have the options of gaining ingormation which is presented interestingly through a variety of media outside the school, surely they should have them in schools as well. Besides, the educational tasks ehich are getting electronic age heavier and more complex in this electrical age, cannot be carried out through lecturing in traditional classrooms where pupils sit still and follow in unison the lecture or what ever presentation is made. It seems inevitable for us to agree to the adoption of media in the teaching learning process, in this case modern media. The writer would to suggest that questions about whather we should adapt new media new media for educators to accept the compound vies on technology. In educational terms this vies means that the introduction of electronic media, for example, will not prove a panacea as the optimists might claim, nor will it necessarily dehumanize, as the pessimists for instance, television may bring the outside world into the schoolroom, but it very likely impose rigid class viewing schedule (Gillett, 1973). The two basic functions of educational media are: informing and developing mental skills (Solomon, 1974). Inthis paper the emphasis woll be put on the discussion of the affective aspevts of the use of media on the learners, on the onterctions among learners themselves, and on the interactions between learners and the teacher. Hopefully, through the discussion clearer eideas about the matter under consideration will be obtained.